The Influence of Young Teachers' and Professional Teachers' Learning Skills on Student Learning Outcomes at SDN 33 Bangai, Torgamba District, South Labuhanbatu Selatan - Syafnan; Juli AZMI; Rika Andriani Ritonga (RADINKA JAYA UTAMA PUBLISHER, 2025)
This aiming For analyze influence skills teaching young teachers and professional teachers to results Study students at SD Negeri 33 Bangai . Using approach quantitative comparative with design ex post facto , data collected through test academic , observation skills teaching , and documentation mark students . The sample consists of from two classes , each taught by a teacher with background behind experience different . Analysis results show that despite average skills teaching young teachers and professional teachers similar , there are difference significant in aspect its implementation . Young teacher superior in use of digital learning media and building interaction , while professional teachers show superiority in management class and delivery systematic material . Average value student classes taught by professional teachers A little more high and consistent . Research This conclude that second teacher group contributes positive to results learn , with characteristics different strengths . Collaboration​ intergenerational teacher support is recommended as a strategy for optimize quality learning at school base